ANALISA KANDUNGAN TIMBAL (Pb) PADA TERASI BERMEREK DAN TERASI HASIL OLAHAN INDUSTRI RUMAH TANGGA YANG DIJUAL DI BEBERAPA PASAR TRADISIONAL DI KOTA MEDAN TAHUN 2013 - ihsan fasri angkat; nurmaini *; wirsal hasan (Lingkungan dan Kesehatan Kerja, 2014)
Analysis of lead (Pb) on branded terasi and terasi producted at home industry were sold in some traditional markets in the Medan city in 2013. Based on composition, terasi (seasoning food is made from fermented shrimp or fish mixed with salt), was divided into fish terasi, shrimp terasi and paste mixture of both. From several previous studies proved that fish and shrimp including marine life which contaminated by heavy metals as a result of marine pollution. This study was descriptive research, to describe the levels of lead (Pb) in terasi, where the objects of study were composed of 10 samples of terasi consists 5 samples of branded terasi and 5 samples of unbranded terasi taken purposively as well as the accept daily intake (ADI) of the terasi. Determination of lead (Pb) using Atomic Absorption Spectrophotometry in Provincial Health Laboratory of North Sumatera.The results showed from five samples of branded terasi, there is one positive contains lead (Pb) (1.80 mg/kg) and didn’t qualify (BPOM’s maximum limit of 1.0 mg/kg), while the other four relatively safe because were under value detection tool (Pb <0.002 mg/kg). For the terasi samples that processed at home industry (unbranded), four samples contains lead (Pb), but only one that was above the maximum limit (1.88 mg/kg), and one sample under value detection tool. Recommended to the local Department of Health and the BPOM of Medan City in order to perform inspection terasi on the market mainly derived from heavy metal polluted waters of the region is quite high. Counseling and overseeing terasi businesses, especially in the home industry. Key words: terasi, lead, traditional market